IMPLEMENTATION OF THE KLANGEN COFFEE & ROASTERY MARKETING PUBLIC RELATIONS STRATEGY IN FORMING A POSITIVE IMAGE IN THE EYES OF THE PUBLIC: IMPLEMENTASI STRATEGI PUBLIC RELATIONS MARKETING KLANGEN COFFEE & ROASTERY DALAM MEMBENTUK CITRA POSITIF DI MATA PUBLIK - Pramasti Adiyatni Pranoto; Niken Ayu Salsabila Putri (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2023)
TThe development of coffee shop business trends in Indonesia has increased over the last few years. Even though Indonesia was hit by the COVID-19 pandemic, it did not discourage businessmen in the industry. In fact, several businessmen started their businesses during the pandemic, including Klangen Coffee & Roastery. As a businessman who operated during the pandemic, Klangen Coffee & Roastery employed a Marketing Public Relations strategy to survive in the competitive coffee shop business and create a positive image in the public eye. This study uses Harold Lasswell's Propaganda theory and a focus method that includes five elements of communication: source, message, channel or media, receiver, and effect. The research aims to understand Klangen Coffee & Roastery's Marketing Public Relations strategy in shaping a positive image in the public eye. The interpretive qualitative research methodology involves conducting in-depth interviews and observations. The study's results suggest that Klangen Coffee & Roastery's Marketing Public Relations strategy has been successful but not yet fully maximized. Researchers also see that the use of content can have a fairly good impact or effect when delivered through Instagram and TikTok.